Digital Referral Patterns for Otolaryngology Subspecialties: A Two-Year Nationwide Analysis in Saudi Arabia - Abdullah A. Alharbi; Meshary S. Binhotan; Ahmad Y. Alqassim; Mohammed A. Muaddi; Abdulaziz Alhosaini; Mohammed S. Arafat; Abdulrahman Aldhabib; Ibrahim Sumaily; Nawfal A. Aljerian (Healthcare, 2026)
Background: Otolaryngology conditions significantly influence public health globally, often posing challenges in accessing specialized ear, nose, and throat (ENT) services. Digital referral systems can facilitate access to specialized care while supporting resource allocation. This study analyzed ENT digital referrals through the digital referral system of the Saudi Medical Referrals Centre to describe utilization patterns across different ENT subspecialties. Methods: This retrospective cross-sectional study analyzed 50,514 ENT digital referrals across Saudi Arabia from January 2023 to December 2024. Crude population-based rates per 10,000 were calculated using national census data. Cross-tabulation tables were utilized to compare patient demographics, regional variables, and referral characteristics with ENT subspecialties. Results: ENT digital referral utilization over two years reached 15.70 per 10,000 population (7.38 in 2023, and 8.32 in 2024). Patients over 60 years showed the highest rates (42.17), followed by children aged 1–7 years (29.90). Females demonstrated a higher crude population-based rate (17.07 vs. 14.83) despite males comprising 57.76% of total referrals. General ENT services represented 59.49% of referrals, audiology services 32.92%, while specialized services showed lower volumes. Routine outpatient referrals predominated at 91.14%, and only 1.3% of total requests required intensive care beds. Most referrals were managed internally (93.75%) with overall acceptance rate reaching 89.41%. Conclusions: The findings demonstrate distinct age- and subspecialty-related utilization patterns within Saudi Arabia’s national ENT digital referral system, with the highest demand among older patients and young children. General ENT constituted the majority of referrals, while other specialized services appeared in smaller volumes. The predominantly outpatient, highly accepted, and internally managed referral patterns establish baseline metrics for national ENT subspecialty access. These findings outline nationwide coordination patterns of subspecialty care and support continued investment in digital health infrastructure for specialized care coordination.